A Neutrosophic Multi-Objective Optimization Framework for Sustainable Design of Water Supply Systems - Jesús Rafael Hechavarría Hernández; Maikel Yelandi Leyva Vázquez (Neutrosophic Sets and Systems)
The study addresses the challenge of optimizing water supply systems (WSS) under conditions of uncertainty, variability, and multiple. In a context where sustainability is a key criterion, traditional Multiobjective optimization approaches are often insufficient to handle the imprecision and indeterminacy inherent in data and models. This work proposes a Neutrosophic Multi-Objective Model (NMM) that integrates Neutrosophic Logic to capture uncertainty in decision variables, objective functions, and constraints. Unlike conventional methods, NMM allows considering degrees of truth, indeterminacy, and falsity, offering a more robust and flexible framework for decision-making in WSS. The relevance of this study lies in its ability to address complex water resources planning and management problems, where economic, social, and environmental sustainability must be balanced under conditions of high uncertainty. Through the application of MMN, optimal solutions are identified that not only minimize costs and losses but also maximize efficiency and service quality, considering variability in demand and risks associated with climate change and infrastructure failures. The results demonstrate that MMN overcomes the limitations of traditional approaches by providing more adaptive and resilient solutions. This research contributes to the field of complex systems optimization by introducing an innovative methodology that combines Neutrosophic Logic with Multiobjective techniques.